Selective Inhibition of Sialic Acid-Based Molecular Mimicry in Haemophilus influenzae Abrogates Serum Resistance. Issue 10 (18th October 2018) - Heise, Torben; Langereis, Jeroen D.; Rossing, Emiel; de Jonge, Marien I.; Adema, Gosse J.; Büll, Christian; Boltje, Thomas J.
Summary: Pathogens such as non-typeable Haemophilus influenzae (NTHi) evade the immune system by presenting host-derived sialic acids. NTHi cannot synthesize sialic acids and therefore needs to utilize sialic acids originating from host tissue. Here we report sialic acid-based probes to visualize and inhibit the transfer of host sialic acids to NTHi. Inhibition of sialic acid utilization by NTHi enhanced serum-mediated killing. Furthermore, in an in vitro model of the human respiratory tract, we demonstrate efficient inhibition of sialic acid transfer from primary human bronchial epithelial cells to NTHi using bioorthogonal chemistry. Graphical Abstract: Highlights: NTHi expresses host sialic acids on its surface to evade the immune system Ac5 SiaNAz enables visualization of host sialic acid transfer to NTHi SiaNAc-3Fax blocks sialic acid incorporation in NTHi, but not in host cells Sialic acid blockade with SiaNAc-3Fax enhances serum-mediated killing of NTHi Abstract : Molecular mimicry of non-typeable Haemophilus influenzae (NTHi) with host sialic acid sugars mediates resistance to serum killing and increases virulence. Heise et al. have developed sialic acid derivatives that allow either visualization or inhibition of host sialic acid transfer to NTHi, the latter enhancing serum-mediated killing.